Study on dynamic wetting and synergistic effect of surfactants on bituminous coal surface in coal mines - Jiangpeng Ju; Ju Zhao (PLoS ONE, 2026)
With the continuous advancement of green mining initiatives in China, dust control during coal mining has become a critical issue for occupational health and ecological environmental safety. In response to the issues of coal dust pollution generated during coal mining and the inefficiencies of water spray dust suppression, this study investigates the fundamental mechanism by which multi-component surfactants synergistically form a stable adsorption layer on bituminous coal surfaces. The research employs macro-scale surface tension measurements, dynamic contact angle analysis, XPS spectroscopy, SEM for microstructural morphology, and molecular dynamics simulations. The results identify the optimal formulation as a 1:1 volume ratio mixture of 0.2% SDS and 0.1% CDEA. The synergistic effect of hydrogen bonding and electrostatic interactions first promotes the formation of a complex between the sulfate group of SDS and the amide group of CDEA. This complex then packs more efficiently, leading to an increased molecular density at the interface. The surface tension of the system is reduced to 35.23 mN/m, while the adhesion work and immersion work of the solution on the bituminous coal surface reach their maximum values. The spreading work is –0.48 mN/m, closest to the threshold of spontaneous spreading. This research offers theoretical support for developing a new generation of high-performance and environmentally friendly dust suppressants.